HE, NE AND AR COMPOSITION OF THE EUROPEAN LITHOSPHERIC MANTLE - Gautheron C.; Moreira M.; Allègre C. (My University, 2005)
Rare gases have been measured in ultramafic xenoliths from European volcanic provinces, Dreiser Weiher (Germany), Massif Central (France) and Kapfenstein (Austria), to characterize the rare gas signature of a proterozoïc subcontinental lithospheric mantle. The helium isotopic results, obtained by crushing of olivines, show values similar to the worldwide olivine xenocrysts and phenocrysts, with a very homogeneous, radiogenic helium isotopic ratio compared to that of the MORB source: 4He/3He=115,000±7600 (R/Ra=6.32±0.39Ra being the 3He/4He atmospheric ratio) compared to ∼90,000 (R/Ra=8) for MORB, for a large range of 4He concentration: 2×10−10 to 6×10−8 ccSTP/g. Neon and argon isotopic ratios show an important air component and nevertheless a mantle component, similar to MORB. The maximum 20Ne/22Ne and 40Ar/36Ar isotopic ratios measured in olivines are 10.65 and 6574, respectively. Elemental 3He/36Ar ratios appear strongly fractionated, suggesting helium diffusive loss from fluid inclusions to mineral matrix. The helium, neon and argon isotopic ratios argue against a lower mantle-derived plume responsible for the European Cenozoic volcanism, which is rather due to crustal extension and melting of the lithospheric mantle. Another possibility is that a mantle plume presently lies under the lithosphere, having triggered secondary plumes of lithospheric material from the lithosphere–asthenosphere boundary. To explain the homogenous helium isotopic signature of the European subcontinental lithospheric mantle, we discuss two possible models where asthenospheric helium invades the lithosphere: recent, local metasomatism and global, continuous metasomatism in steady state for helium. In the latter model, the derived 4He flux is consistent with helium fluxes estimated for large areas such as the Pannonian basin and the Eger rift. The atmospheric component seen in Ne and Ar data is likely due to important air contamination of the xenoliths close to the surface, but may partly be possible evidence for subduction of atmospheric rare gases. Therefore, it is not meaningful to apply the steady state model to Ne and Ar.
Keywords: Rare gases; Helium flux; Mantle xenoliths; Subcontinental mantle; Europe